The Jury in England: Practice and Ideology - DUFF, Peter (Institutional Knowledge at Singapore Management University, 1982)
One of the ideological functions of the jury is its demonstration of the impartiality and independence of decisions affecting the accused through its role of arbiter in the adversary system. A second ideological function of the jury is to maintain community involvement in the decision making of state institutions that exercise control over citizens. The state buttresses its legitimacy by showing that the 'people' ultimately determine how the powers of the state are exercised. In its functioning, however, the jury may be either restricted in its independence or manifest partiality. The power of the judge to influence a jury greatly obstructs its independence, as matters of law are so interpreted by the judge to the jury that it may be strongly guided in its decision making. Further, the jury's reflection of community attitudes and perspectives in its representativeness does not in itself constitute impartiality so much as it reflects the partiality and biases of the majority of citizens, who may be ill-equipped to render impartial judgments on persons representing community minorities whose appearance, values, and beliefs may be different from the majority of jury members. Four notes and thirteen references are provided.